ANALISIS PENGGUNAAN TERTINGGI DAN TERBAIK ATAS TANAH KOSONG DI JALAN PANGERAN MANGKUBUMI YOGYAKARTA (HPL 001 PT. ANINDYA MITRA INTERNASIONAL) - LA MAHA, HARTONO LA MAHA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The highest and best use research for the vacant land HPL 001 PT. Anindya Mitra International street of Pangeran Mangkubumi Yogyakarta, conducted with analysis of property productivity in law aspect, regulation and also aspect of physical and location using the threshold testing and rating grid so it can be obtained a possible alternative usage. Thus, conducted with supply, demand market analysis, and finance feasibility analysis for each usage proposal. In this research, the data to be analyzed consist of primary data secondary data. Primary data containing the incomes data, rent and expenditure that raised to be an alternative size measure, treadâs form, topography, utility and others was obtained through direct observation. Secondary data was obtained from Statistical Center Organization (BPS) and governmentâs institutions in Yogyakarta. From the result of the analysis was gained three competent and possible farm usage proposal that is the use of hotel, traditional market, and parking area. Based on the indicator of finance feasibility by Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PBP), Rate Return on Investment (ROI), and Benefit Cost Ratio (BCR). Thus, the use of hotel to be better indicated comparing to traditional market and parking area so that can be concluded that the alternative using of hotel represent the most optimal.